Negacja autorytetów i pogarda a społeczeństwo masowe - Cwynar, Katarzyna M. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The author takes up the problem of the negation of authorities in mass society. She points to their significance so far and the premises of their contemporary negation. Not without significance in this case is the issue of rejecting higher values in favour of the pragmatisation of life and the formation of a mass society, whose main principle is mediocrity. The aim of the considerations is to indicate the manifestations of contemporary processes resulting in the negation of authorities of an axiological nature, and the contempt for higher values. They are reflected in such areas of culture as science, art, politics and religion.
The negation of authorities and the contempt in mass society
Keywords: authority; society; mass culture; mediocrity; contempt